2008
DOI: 10.1002/masy.200850205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in Swelling Solutions Modifying Cellulose Fiber Reactivity – Part 1: Accessibility and Sorption

Abstract: Summary: Of prime importance in reactions involving insoluble cellulosic fibers is the sorption of reagents, which is governed by their degrees of accessibility in substrates. Swelling treatments of cellulosics in alkali solutions alter substrate accessibility leading to changes in their reactivity. In this paper, the first of a two-part series, we collate and examine the results from various studies involving different techniques to characterize modifications in cellulosic fibers after swelling treatments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…WRV is an easily measurable parameter and can reflect the change of pore size due to hornification. It was found that WRV can correlate well with pore radius (Andreasson et al 2003) and pore volume (Jaturapiree et al 2008), or the amount of water in cell wall pores (Hui et al 2009;Weise et al 1996). Furthermore, it was found that WRV can correlate well with SED as reported in our previous study (Luo and Zhu 2011).…”
Section: Resultsmentioning
confidence: 59%
“…WRV is an easily measurable parameter and can reflect the change of pore size due to hornification. It was found that WRV can correlate well with pore radius (Andreasson et al 2003) and pore volume (Jaturapiree et al 2008), or the amount of water in cell wall pores (Hui et al 2009;Weise et al 1996). Furthermore, it was found that WRV can correlate well with SED as reported in our previous study (Luo and Zhu 2011).…”
Section: Resultsmentioning
confidence: 59%
“…1,2 However, the strong swelling propensity of lyocell fibers in alkali solutions 3 changes substrate properties and may lead to alterations in the accessibility and reactivity of lyocell for chemicals and reagents and influence its performance in subsequent treatments. 4,5 In earlier work, 6,7 we examined the influence of alkali pretreatments on the performance of lyocell fabrics in subsequent resin finishing treatments. Fabric samples were pretreated with sodium hydroxide (NaOH; 120 g/L) or KOH (250 g/L) and resinfinished with a dimethyloldihydroxyethylene urea (DMDHEU) based product.…”
Section: Introductionmentioning
confidence: 99%
“…However in aqueous solution, fibre microstructure in amorphous regions seems to play the more relevant role in M 2+ adsorption. Metal ion complexation can be expected to occur in the amorphous regions of the fibres (Ibbett et al 2007;Jaturapiree et al 2007;Bui et al 2007). As crystallinity will affect the accessibility to reactive sites, a negative correlation between Zn 2+ complexation and degree of crystallinity would be expected.…”
Section: Mn 2+ -Complexesmentioning
confidence: 96%